Do numbers exist? : a debate about abstract objects - Van Inwagen, Peter; Craig, William Lane (New York, NY : Routledge, 2024)
In Do Numbers Exist? Peter van Inwagen and William Lane Craig take opposite sides on whether there are abstract objects, such as numbers and properties. Craig argues that there are no abstract objects, whereas Van Inwagen argues that there are. Their exchange explores various arguments about the existence and nature of abstract objects. They focus especially on whether our ordinary and scientific thought and talk commit us to abstract objects, surveying the options available to us and the objections each faces. The debate covers central problems and methods in metaphysics, and also delves into theological questions raised by abstract objects. Key Features: Showcases the presentation and defense of two points of view on the existence of abstract objects, from two of the world's leading philosophers Presents definitions in an easily accessible form Provides frequent summaries of previously covered material Includes a glossary of all specialized vocabulary
Keywords: Number theory; Abstraction; PHILOSOPHY / General